ANALISA KONSERVASI ENERGI SELUBUNG BANGUNAN BERDASARKAN SNI 03-6389-2011. STUDI KASUS: GEDUNG P1 DAN P2 UNIVERSITAS KRISTEN PETRA SURABAYA - Ricky Gendo; Jimmy Priatman; Sandra Loekito (Dimensi Utama Teknik Sipil, 2015)
Nowadays, people talk a lot about energy crisis problem. In fact, demand for energy grows every year while this growing demand is not matched by the growth of the energy source. As the impact, future generation will possibly face energy crisis. In Indonesia, the effort to conserve energy still has not been considered by many parties. Just in these recent years, Greenship certification which is awarded by GBCI (Green Building Council Indonesia) to certified green buildings in Indonesia, started to be recognized by project stakeholders and moreover in short time, Greenship will be one of requierements for applying building permit (IMB) in Surabaya. OTTV (Overall Thermal Transfer Value) calculation is one of criteria in Greenship assessment, where heat transfer through the whole building envelope is minimized to reduce building cooling load. The maximum value of OTTV is 35 W/m2 based on SNI 03-6389-2011. This research is conducted to study whether the OTTV of P1 and P2 of Petra Christian University Surabaya building has met this standard or not. If not, OTTV will be minimized by considering the facade material selection.